Seasonal variation of potential gradient in the free atmosphere at Poona during the I.G.Y. - MANI, ANNA; HUDDAR, B. B.; KACHARE, N. R.; SWAMINATHAN, M. S.; SRIVASTAVA , G. P.; VENKITESHWARAN, S. P. (MAUSAM, 1960)
Measurements of atmospheric electricity in the regions near the surface of the earth are influenced variously by factors peculiar to local conditions, e.g., there are very often temperature differences giving rise to convection currents producing turbulent mixing of the air throughout this portion of the atmosphere.